The influence of 1-α-oxycholesterol with antioxidants and calcium phosphate on the development of experimental periodontitis in rats - Schneider, S. A.; Suslova, O. V.; Saveleva, N. N.; Gorohivsky, V. N.; Tkachenko, E. K. (Journal of Education, Health and Sport, 2020)
In experiments on 26 rats the influence of complex 1-α-oxycholesterol with antioxidants and calcium phosphate. The study was conducted on the background modeling of periodontal disease through a combination of prooxidants delagila and etilendiaminova acid chelating agent (EDTA).